Latviešu studentu korporācijas Tervetia krāsu deķelis - Rubenis, Rūdolfs (LU Muzejs, 2022)
Raksts tapis par godu latviešu studentu korporācijas "Tervetia" Simtgadei 30.04.2022, kas veltīts vienai no tās regālijām - krāsu deķelim. Tiek aprakstīta krāsu deķeļa saglabāšana Latvijas Universitātes Muzejā, tā simboliskā nozīme un pieejamība sabiedrībai. Tiek skaidrots arī paša krāsu deķeļa izmantošanas reglaments, ko ikdienā ievēro pašas studentu korporācija biedri.

This article was written on the occasion of the 100th Anniversary of the Latvian Student fraternity "Tervetia" 30.04.2022, which is dedicated to one of its Regalia - the Colour Deckel. The conservation of the Colour Deckel in the Museum of the University of Latvia, its symbolic meaning and its accessibility to the public are described. The regulations for the use of the Colour Deckel itself, which are observed on a daily basis by the members of the Student fraternity, are also explained.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Studenti; Studentu korporācijas; Tervetia; Regālijas; Konservācija; Students; Student fraternities; Tervetia; Regalia; Conservation